2007
DOI: 10.1007/s11064-007-9317-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytoglobin Up-regulated by Hydrogen Peroxide Plays a Protective Role in Oxidative Stress

Abstract: Cytoglobin (Cygb) is a recently discovered intracellular respiratory globin, which exists in all types of cells. It has been suggested that Cygb has a role in protecting cells against oxidative stress. In the present study we have tested this hypothesis. The N2a neuroblastoma cells were exposed to various kinds of insults, including hydrogen peroxide (H(2)O(2)), hypoxia, kainic acid, high extracellular CaCl(2), high osmolarity, UV irradiation and heat shock. Among them, only H(2)O(2)-treatment induced a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 29 publications
2
71
0
1
Order By: Relevance
“…Recent studies of neuronal cancer cells support the finding of the antioxidative stress effects of Cygb. 10,11 In addition to Cygb, recent studies reported that hemoglobin 28 and myoglobin 45 also scavenge radicals, which emphasizes a role for globin proteins as antioxidants. Collectively, these in vitro studies suggest a novel antioxidative role for globins in addition to their known conventional facilitation of oxygen transport, and support the finding that Cygb serves as a defensive mechanism against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of neuronal cancer cells support the finding of the antioxidative stress effects of Cygb. 10,11 In addition to Cygb, recent studies reported that hemoglobin 28 and myoglobin 45 also scavenge radicals, which emphasizes a role for globin proteins as antioxidants. Collectively, these in vitro studies suggest a novel antioxidative role for globins in addition to their known conventional facilitation of oxygen transport, and support the finding that Cygb serves as a defensive mechanism against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In Ngb-transgenic mice, although infarct volume is reduced, long-term improvement in limb deficits after stroke does not occur [22] . We previously reported that Ngb gene expression is not altered in N2a cells following H 2 O 2 treatment [23] . These studies argue against the proposed protective role of Ngb.…”
Section: Introductionmentioning
confidence: 90%
“…Ngb-siRNA plasmid construction and identification Ngb siRNA expression vectors (named Ngb-siRNA) targeted to different regions of mouse Ngb cDNA (gi:18999491) were constructed using a GFP-expressing siRNA vector (p-Genesil-1, Wuhan Genesil Biotechnology, China), as previously reported [23] . The efficiency of Ngb-siRNA plasmids was confirmed by cotransfecting Ngb-siRNA and p-Ngb-EGFP plasmids [18] at a ratio of 4:1 into N2a cells using LipofectAMINE TM 2000 reagent (Invitrogen Life Technology, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cygb is ubiquitously expressed [3,20], and is upregulated in rat heart and liver following hypoxia [49] or in brain by hypoxia [10]. When Cygb mRNA was knocked down by siRNA, cell death was increased upon hydrogen peroxide-treatment [35], suggesting that Cygb protects cells against oxidative stress. In addition, Ngb expression was up-regulated following hypoxic challenges [54] and in ischemic-hypoxia brain injury [53].…”
Section: Cystatin B (Cstb)mentioning
confidence: 99%